Influence of mental health service provision on the perceived quality of life among psychiatric outpatients: associations and mediating factors - Lundqvist, Lars-Olov; Rytterström, Patrik; Rask, Mikael; Brunt, David; Sellin, Tabita; Grim, Katarina; Rystedt, Ingrid; Schröder, Agneta (Frontiers in Psychiatry, 2024)
Objective: To investigate the relationship between perceived mental health service provision and quality of life (QOL) as perceived by patients in psychiatric outpatient care.Methods: A total of 373 adult patients registered at 15 psychiatric outpatient clinics in three regions in central and southern Sweden were included in the study. Survey data were collected using a questionnaire on mental health service provision, symptom severity, recovery, clinical diagnosis, sociodemographics (serving as independent variables) and QoL (serving as the dependent variable). Three aspects of mental health service provision were used: patients' perceived quality of care, perceived staff-patient interaction, and patient reported psychiatric treatments. Structural equation modelling was used to model the relationship among the variables.Results: Variables in mental health service provision showed few direct associations with patients' perceived QoL. Instead, the associations of mental health service provision on QOL were mainly mediated through symptom severity and recovery. These relationships were retained after adjusting for sociodemographic variables and clinical diagnoses. The final model achieved excellent goodness of fit (χ2 = 49.502 p = 0.230, RMSEA=0.020, CFI = 0.997 and a SRMR= 0.024).This study shows that mental health service provision is associated with patients' perceived QoL; however, this association is mostly indirect and mediated by reduced symptom severity and increased recovery. This finding can help inform the design of future interventions to enhance service provision to improve patients' QoL.